Re-evaluation of Architectural Heritages and Japanese Traditional Houses: The Case of Osaka Open-Air Museum of Old Japanese Farm Houses - Gulec, Fatma Esra (Journal of History Culture and Art Research, 2022)
Since the beginning of the twentieth century, as a result of the increase in the number of people who cannot find their hopes in the cities and who question the stresses of the new city life, the interest in rural life has increased, and rural culture and architecture have also received their share, like many traditional elements that are in danger of extinction. The idea of ​​preserving and re-evaluating traditional architecture has become even stronger in countries where industrialization and migration from rural to urban have been experienced, especially in the years following World War II. As a result, conservation and evaluation practices have become widespread in the world through the preservation of rural architectural elements in situ or the open-air museums created by taking them from their original places and moving them closer to the cities. Thus, together with the preservation of rural culture, it was aimed to eliminate the curiosity of the people of the city about rural culture and architecture. In Turkey, as in the example of Altınköy, interest in open-air museums related to rural life is increasing. With the projects to be done, it is possible to go beyond the purpose of recreation, to preserve the rural architecture and to keep the culture alive. There are successful examples of this in Japan. For this reason, this article deals with the conservation and re-evaluation of rural architecture through the example of Japan, with the desire to set an example for Turkey. Therefore, in this article, literature review, on-site observation, examination and documentation method were used. Open Museum in Osaka and the rural architectural elements in it were examined within the scope of carrying and re-evaluating the tangible and intangible cultural heritage to the cities and new generations.